Factors influencing exchange rate for selecting Asian countries / Nur Nadzirah Rosli - Rosli, Nur Nadzirah (Faculty of Business and Management, 2020)
This research to investigate factors influencing exchange rate for four (4) Asian countries. The factors influencing which is fluctuations of inflation rate, interest rate, changes of export and import. The panel data of 31 years from 1987 until 2017 has been use for this study. In this research also cover 4 Asian countries which is China, Indonesia, Malaysia and Philippines. However, the result to investigate the relationship between exchange rate and other variables, is an exchange rate depend on others variables? Through this research to examine the relationship between all the independent variables and dependent variable which exchange rate, independent variable such as inflation rate, interest rate and import. Thus, to get the result for this study the researcher is use EViews to run all test inside.